Deteksi Dini Risiko Stunting Pada Wanita Usia Subur Prakonsepsi (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2023)
The period of the first 1000 days of life was a vulnerable period for children to experience stunting, starting from pregnancy until the child is 2 years old. Nutritional status during the preconception period can affect pregnancy and the welfare of the baby, so it needs to be maximized before pregnancy. This study aims to conduct early detection of stunting risk in women of childbearing age preconception in the city of Parepare. The type of research used was descriptive. The sample in this study were some of the prospective brides at the Office of Religious Affairs in Parepare City. The sampling technique using the Purpossive Sampling method was 50 people. Data collection was carried out from March to May 2022. The nutritional status of the prospective bride and groom was obtained through measurements of upper arm circumference and hemoglobin levels. The results showed that 46% of the brides-to-be had Chronic Energy Deficiency (KEK) and 38% had anemia. According to the level of knowledge about nutrition, 10% have low knowledge and 62% have moderate level of knowledge. It was suggested the need for education to women of childbearing age preconception and improvement of nutritional status to prevent the risk of stunting, especially in the first 1000 days of.